Using fracture energy to characterize the hot mix asphalt cracking resistance based on the directtensile test - Lubinda F. Walubita; Allex E. Alvarez; Flor Sanchez (Revista Facultad de Ingeniería Universidad de Antioquia, 2012)
Cracking is currently one of the most common distresses in hot mix asphalt (HMA) pavements, often costing the highway agencies million of dollars in maintenance and rehabilitation activities. Laboratory characterization of HMA cracking resistance thus constitutes a fundamental step in mix-design and analysis to ensure adequate Æ eld performance in terms of this distress. This study assesses the suitability of analyzing the HMA cracking resistance using fracture parameters determined based on the direct tension test, which include the fracture energy. Corresponding results suggest that the fracture energy and the proposed fracture energy indices has promising potential to be used as fracture parameters to discriminate the cracking resistance potential of HMA mixes in the laboratory. More research is recommended to further reÆ ning this concept and relate to Æ eld cracking resistance data.